Ontario's stroke report cards: Cross-continuum data linkage allows evaluation of system of care. (2018) - Hall, Ruth; Khan, Ferhana; Levi, Jen; Ma, Huiting; Martin, Cally; Moher, Cheryl; Kelloway, Linda; Linkewich, Elizabeth; Bayley, Mark
No abstract available